Effect of selenylation modification on antitumor activity of peptidoglycan from Lactobacillus acidophilus. (1st June 2017) - He, Jiayi; Wu, Zhen; Pan, Daodong; Guo, Yuxing; Zeng, Xiaoqun
Highlights: Amadumbe starch nanocrystal (SNCs) were square-like platelets: size: 50–100 nm. Amadumbe SNCs exhibited A-type crystallinity pattern, similar to native starch. SNCs improved thermal stability, WVP and TS of composite starch films. Composite amadumbe starch films had better WVP and TS than did potato films. Better interaction between SNCs and starch of the same botanical origin was observed. Abstract: Selenium is an essential trace element for human with the antitumor properties. In the present study, the peptidoglycan (PG) derived from Lactobacillus acidophilus was modified by selenylation with the HNO3 -Na2 SeO3 method. Reaction temperature, reaction duration and the selenide content were optimized according to orthogonal design of three-factors. In addition, the molecular structure of selenizing peptidoglycan (Se-PG) was determined by infrared spectroscopy analysis. Furthermore, the antitumor activity of Se-PG was also investigated in HT-29 cells. The results showed that Se-PG exerted a greater antitumor activity than non-modified PG in a dose-dependent manner. These findings indicated that selenylation modification can enhance the antitumor activity of PG, and Se-PG could achieve its potential in antitumor activity.